(3JYdjb Ydi GdQSGdI GdecfjI HCMhGd GdcfjI cjfIs ((3eMeO Hf eMeO Hf eMeO GdhRjQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CXgQ aj NHGjG GdOhGA CSQGQ GdTaGA hHYO abO hbY GdfXQ aj QhVI gPg GdQSGdI ahLOJgG fRgI GdYdjd hJHUQI hTaGA GdVdjd hJPcQI s
(3BNQgG (B:s
(3Gfc cdeG bGHdJ eMehekG HbOQ bGHdJgG HQOkG hSdGekG s
(3Vef eLehY , JQJjHgG (B: 7s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs